Electrode laminated with ion-selective blocking layer for use in vanadium redox flow batteries - Mara , Muhammad Ikhsan; Abbas, Saleem; Choi Seung-Young; Huy, Do Xuan; Ha, Heung Yong; Bentien, Anders; Azizi, Kobra; Hjuler, Hans Aage; Henkensmeier, Dirk (Elsevier, 2023)
2 μm thick meta-polybenzimidazole (PBI) films effectively block permeation of vanadium ions in vanadium redox flow batteries, but are usually reinforced with supports to guarantee mechanical stability. Here, we eliminate the use of an additional support by laminating a 2 μm thick 10-wt% dibromoxylene crosslinked PBI layer directly on carbon paper. The total area specific resistance (ASR) of the two PBI films is 156.8 mΩ cm2 in 1.5 M V4+/3 M sulfuric acid solution, 26 % lower than that of Nafion 211. VRFB cells are made by assembling a membrane between two PBI-laminated carbon paper electrodes. These electrodes simplify membrane selection, because high selectivity is not anymore required, and chemical stability of the membranes against VO2+ is less crucial. An example cell is made with a 70 μm thick Gel PBI membrane. Membrane and PBI layers exhibit an ASR of 177.8 mΩ cm2 in 1.5 M V4+/3 M sulfuric acid solution, 18 % lower than that of Nafion 211. The selectivity of proton over vanadium ion is 4.2 × 1014 S s m？3, 9 times better than that of Nafion 211. In a VRFB, a stable energy efficiency of 87.6 % at 75 mA cm？2 compared to 82.3 % for Nafion 211 is obtained.